2021
DOI: 10.1186/s12887-021-02574-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of problematic feeding in young children born prematurely: a meta-analysis

Abstract: Background Difficulties related to eating are often reported in children born preterm. The objective of this study was to quantitatively synthesize available data on the prevalence of problematic feeding in children under 4 years of age who were born preterm. Methods Literature was identified from PubMed, CINAHL, and PsycInfo. The search was limited to English language and publication years 2000–2020. To be included in the meta-analysis, the articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 56 publications
0
43
0
1
Order By: Relevance
“…Mesmo assim, em recente revisão sistemática da literatura, os autores pautados nas evidências encontradas afirmam que os problemas com a alimentação são altamente prevalentes entre crianças nascidas prematuramente nos primeiros quatro anos de vida, independentemente do grau de prematuridade. Dessa forma, esses resultados indicam que os profissionais de saúde durante o acompanhamento de crianças PT devem fazer a triagem para problemas com a alimentação desde a primeira infância, considerando que esta é uma complicação potencial do nascimento prematuro (Pados et al, 2021).…”
Section: Discussionunclassified
“…Mesmo assim, em recente revisão sistemática da literatura, os autores pautados nas evidências encontradas afirmam que os problemas com a alimentação são altamente prevalentes entre crianças nascidas prematuramente nos primeiros quatro anos de vida, independentemente do grau de prematuridade. Dessa forma, esses resultados indicam que os profissionais de saúde durante o acompanhamento de crianças PT devem fazer a triagem para problemas com a alimentação desde a primeira infância, considerando que esta é uma complicação potencial do nascimento prematuro (Pados et al, 2021).…”
Section: Discussionunclassified
“…Figure 2 shows the phases of swallowing, normal actions in each phase, disruptions to swallowing, and their clinical presentation. In the neonatal period, feeding problems can present with diverse clinical manifestations, as shown below, leading to inadequate nutritional intake, increased length of hospitalization, and compromised airway safety [ 9 , 10 , 16 ].…”
Section: Understanding Oral Feeding and Feeding Problems In Preterm Infantsmentioning
confidence: 99%
“…While previous studies have suggested that up to 1% of the pediatric population can present with feeding problems, the prevalence is likely to be significantly higher in preterm infants, proportional to the degree of prematurity [ 15 ]. Residual feeding problems in growing preterm infants span a broad spectrum of phenotypes, including feeding tube dependency [ 30 ], non-specific feeding difficulties, oral aversion [ 9 , 31 , 32 ], feeding aversion, poor progression to solid foods, challenges with eating specific food types (e.g., solids), and subtle swallowing difficulties.…”
Section: Feeding Problems In Preterm Infants Beyond the Nicumentioning
confidence: 99%
See 2 more Smart Citations